2016
DOI: 10.1007/s00204-016-1918-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 31 FDA approved small-molecule kinase inhibitors on isolated rat liver mitochondria

Abstract: The FDA has approved 31 small-molecule kinase inhibitors (KIs) for human use as of November 2016, with six having black box warnings for hepatotoxicity (BBW-H) in product labeling. The precise mechanisms and risk factors for KI-induced hepatotoxicity are poorly understood. Here, the 31 KIs were tested in isolated rat liver mitochondria, an in vitro system recently proposed to be a useful tool to predict drug-induced hepatotoxicity in humans. The KIs were incubated with mitochondria or submitochondrial particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 25 publications
3
51
1
Order By: Relevance
“…Since sorafenib causes cardiotoxicity necessitating drug discontinuation in some patients (Schmidinger et al, ; Hall et al, ; Escalante et al, ), as well as liver toxicity associated with mitochondrial dysfunction in rodents (Zhang et al, ), we applied a non‐targeted metabolomics analysis using GC/MS to both the heart and liver after 2 weeks of treatment that induced cardiac toxicity (Figure ). We assayed skeletal muscle (quadriceps femoris) and plasma collected in parallel to identify if myocardium and striated muscle metabolism are affected similarly and if any of these observed alterations could be monitored by any biomarkers in the plasma.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since sorafenib causes cardiotoxicity necessitating drug discontinuation in some patients (Schmidinger et al, ; Hall et al, ; Escalante et al, ), as well as liver toxicity associated with mitochondrial dysfunction in rodents (Zhang et al, ), we applied a non‐targeted metabolomics analysis using GC/MS to both the heart and liver after 2 weeks of treatment that induced cardiac toxicity (Figure ). We assayed skeletal muscle (quadriceps femoris) and plasma collected in parallel to identify if myocardium and striated muscle metabolism are affected similarly and if any of these observed alterations could be monitored by any biomarkers in the plasma.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies of 31 small‐molecule KIs approved for use in humans as of November 2016 found that sorafenib was one of three KIs that were hepatotoxic at concentrations equal to the C max and indicated that mitochondrial toxicity was likely contributing to the liver toxicity (Zhang et al, ). Treating animals with sorafenib decreases body weight, an effect also reported in humans, suggesting that sorafenib treatment may lead to fundamental alterations in metabolism (Duran et al, ; Kuczynski et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, as far as TKI are concerned, very few data support the role of RM rather than the parent drug in TKI‐induced hepatotoxicity; these cases are discussed in this section. However, reporting the current state of knowledge of the entire spectrum of toxicity mechanisms at a cellular level is beyond the scope of this review …”
Section: Tki Hepatotoxicity: Evidence Of Rm Involvementmentioning
confidence: 99%
“…Specific features identify drugs associated with high rates of DILI and positive rechallenge: daily dose exceeding 50 mg, predominant hepatic metabolism, hepatocellular injury, and evidence of immunoallergic injury or mitochondrial impairment in vitro . Hepatotoxicity is evident in most drugs with preclinical testing exhibiting: reactive metabolites, marked metabolism‐dependent cytochrome p‐450 inhibition (with >5‐fold change in IC 50 ), covalent protein binding (≥200 pmol eq/mg protein), reactive oxygen species, glutathione adduct formation, lipophilicity (logP≥3), BSEP inhibition, cellular ATP depletion, mitochondrial toxicity, or cytotoxicity .…”
Section: Drug Characteristics Influence Dili and Positive Rechallengementioning
confidence: 99%